Determination of Sensitivity and Specificity of Modified Alvarado Score and Ultrasonography in Patients with Acute Appendicitis - Nishikant Gujar; Sajid Mudhol; Ravi Kumar Choudhari; Sachin D.M. (Journal of Krishna Institute of Medical Sciences University, 2015)
Background: In spite of improvement in modern diagnostic technology, diagnosis of appendix based on clinical suspicion, leads to removal of normal appendix some time, Modified Alvardo Score system is helpful in minimizing same. Aim: To evaluate the sensitivity and specificity of Modified Alvarado Score (MAS) and Ultrasonography (USG). Material and Methods: 350 patients suspected of acute appendicitis were admitted, investigated and treated. They were evaluated using Modified Alvarado Scoring and all cases were subjected to ultrasonography. The sensitivity and specificity of Modified Alvarado Score and Ultrasonography were correlated with histopathological findings. Results: Modified Alvarado score >7 were seen in158 patients in whom 151(95.60%) were histopathologically proved acute appendicitis and 7 (4.43%) patients were histopathologically negative. Modified Alvarado score <7 was observed in 192 patients among whom 81 (42.19%) were histopathologically proved acute appendicitis and 111 (57.81%) patients were histopathologically negative. Among 150 those with Modified Alvarado Score > 7, 152 (96.2%) were ultrasonographically diagnosed as acute appendicitis and 6(3.8%) patients were ultrasonography negative. Among 192 patients those with Modified Alvarado Score <7, 97 (50.52%) were ultrasonographically diagnosed as acute appendicitis and 111 (57.8%) patients were histopathologically negative. Conclusion: Thus it has applying Modified Alvarado Scoring system preoperatively as a protocol in patients with suspected appendicitis. The sensitivity is 98.44% for MAS and 98.33% for USG and specificity is 94.4% for Modified Alvarado Scoring and 90% for USG. In acute appendicitis, MAS is a good diagnostic indicator, and it is highly sensitive in diagnosis of appendicitis. Combined use of MAS and USG is very effective in diagnosis of appendicitis and it helps in reducing number of negative appendicectomy.